HEMOPTYSIS: HOW TO MANAGE ? - Dhaliwal, R S (Journal of Universal College of Medical Sciences, 2016)
Hemoptysis is the expectoration of blood coming from tracheobronchial tree or pulmonary parenchyma. It is one important symptom which brings the patient to a doctor quickly as it frightens the patient and his family very much. It may be streaky or massive ( more than 600ml in 24 hrs ) which can be dangerous to life. Pulmonary tuberculosis remains number one cause of hemoptysis in developing countries. CT Scan chest and bronchoscopy can give most of information in these patients. Massive hemoptysis is life threatening and requires prompt treatment. Number of endobronchial techniques like ice cold saline lavage, balloon tamponade and bronchial artery embolization have been devised to temporarily control hemoptysis. Surgery remains the treatment of choice and pulmonary resection has been the most effective method for control of massive hemoptysis and prevention of recurrent hemoptysis in majority of patients. Surgical rather than medical methods reduce patient's mortality rates due to massive hemoptysis. Newer technique of physiological lung exclusion2 has given much better results than standard lung resection for hemoptysis with minimal mortality and morbidity.